Reforming the Western Australian State Tax Anti-Avoidance Strategy - Wilson-Rogers, Nicole (University of New South Wales, Faculty of Law. Atax, 2012)
The Australian Review of Business Taxation (“RBT”)1 provides that tax avoidance occurs where there is a misuse of the law, such as the exploitation of loopholes in the legislation, to achieve a tax outcome that was not intended by parliament. Tax avoidance presents an unremitting challenge to the integrity of a revenue base and for tax administrators globally.2 In Australia, tax is levied at state, territory and federal levels and consequently, tax avoidance is a problem that affects administrators at all levels of government. As a result, the tax avoidance strategy of state tax administrators can be informed by analysing the methods adopted by their counterparts in other states, territories and by the Commonwealth.3 This paper considers the Western Australian (“WA”) state tax anti-avoidance strategy and argues that it can be strengthened in three key respects: (i) consideration should be given to adopting a uniform general anti-avoidance rule (“GAAR”) based on a refined version of Chapter Seven of the Duties Act 2008 (“Duties Act”). This should apply across the three main WA taxes: duties, pay-roll tax and land tax and be located in the Taxation Administration Act 2003 (WA) (“WA TAA”);4 (ii) the terms of Chapter Seven should be amended and used as the basis of the new uniform GAAR. The amendments should adopt elements of Part IVA in the Income Tax Assessment Act 1936 (Cth) (“ITAA 1936”) including any further refinements adopted by the Commonwealth government, key aspects of other state and territory GAARs and two of the recommendations in the RBT;5 and (iii) WA should enact a promoter penalty regime based on the Commonwealth promoter penalty regime in Division 290 of the Taxation Administration Act 1953 (Cth) (“TAA 1953”).Part one of this paper analyses and discusses the current tax avoidance strategy adopted in WA. This includes a detailed discussion of the GAAR in Chapter Seven of the Duties Act. Part two advocates the implementation of the three key reform measures outlined above to enhance the WA anti avoidance strategy. Part three concludes. Notably, references to other state taxation legislation is made in the context of the ensuing discussion. Appendices 1 and 2 draw on the recommendations made in Part two and outline (respectively) the elements that should form a WA uniform GAAR and promoter penalty regime. Although this paper is written in the WA context the suggestions that are advocated could similarly apply to other state jurisdictions that adopt a similar tax structure to WA. Observations are made throughout the paper regarding the relevance of the recommendations to other Australian states and territories.